Metabolomic Tools to Assess the Chemistry and Bioactivity of Endophytic Aspergillus Strain. Issue 10 (4th October 2017) - Tawfike, Ahmed F.; Tate, Rothwelle; Abbott, Gráinne; Young, Louise; Viegelmann, Christina; Schumacher, Marc; Diederich, Marc; Edrada‐Ebel, RuAngelie
Abstract : Endophytic fungi associated with medicinal plants are a potential source of novel chemistry and biology that may find applications as pharmaceutical and agrochemical drugs. In this study, a combination of metabolomics and bioactivity‐guided approaches were employed to isolate secondary metabolites with cytotoxicity against cancer cells from an endophytic Aspergillus aculeatus . The endophyte was isolated from the Egyptian medicinal plant Terminalia laxiflora and identified using molecular biological methods. Metabolomics and dereplication studies were accomplished by utilizing the MZmine software coupled with the universal Dictionary of Natural Products database. Metabolic profiling, with aid of multivariate data analysis, was performed at different stages of the growth curve to choose the optimized method suitable for up‐scaling. The optimized culture method yielded a crude extract abundant with biologically‐active secondary metabolites. Crude extracts were fractionated using different high‐throughput chromatographic techniques. Purified compounds were identified by HR‐ESI‐MS, 1D‐ and 2D‐NMR. This study introduced a new method of dereplication utilizing both high‐resolution mass spectrometry and NMR spectroscopy. The metabolites were putatively identified by applying a chemotaxonomic filter. We also present a short review on the diverse chemistry of terrestrial endophytic strains of Aspergillus, which has become a part of our dereplication work and this will be of wide interest to those working in this field. Abstract :